Healthy Living To Dismiss Covid-19 In Economic Crisis - R Mochamad A (Jurnal MIDPRO, 2020)
The study is aimed at analyzing how to live a healthy life in the Covid-19 and economics related to Islam and theory H. Health can have an effect on one's economy, as growth in economic development will improve with good quality of life. The approach used in this research is the research of the library through researching, analyzing and reading the literature on how to lead a healthy life in Islam which is linked to Covid 19 and the economy. The results of the analysis show that on the importance of maintaining hygiene in everyday life , health and Islam have the same view. The economic crisis is the impact of Covid-19 to get a new normal life.